Analisis Sistem Pengendalian Intern Persediaan Obat di Rumah Sakit Umum Daerah I.A Moeis - Murniati, - - (EKONOMIA, 2019)
Inventory internal control is an action taken to direct activities so that the objectives can be achieved effectively, efficiently and economically, all resources can be utilized and protected, data and reports can be trusted and presented fairly, and compliance with all applicable regulations. If the control information system that is run by a business entity does not apply the elements of the internal control system and does not relate to each other harmoniously, the effectiveness of internal control of inventory will be difficult to achieve because one of the main objectives of internal control information systems is to improve internal control.               The purpose of this study was to determine whether the system of planning and controlling drugs in the unit of pharmacy installation of RSUD I.A Moeis Samarinda. Based on the formulation of the problem and the basis of the theory that has been stated in this study is the control of drug supplies iInventory internal control is an action taken to direct activities so that the objectives can be achieved effectively, efficiently and economically, all resources can be utilized and protected, data and reports can be trusted and presented fairly, and compliance with all applicable regulations. If the control information system that is run by a business entity does not apply the elements of the internal control system and does not relate to each other harmoniously, the effectiveness of internal control of inventory will be difficult to achieve because one of the main objectives of internal control information systems is to improve internal control.               The purpose of this study was to determine whether the system of planning and controlling drugs in the unit of pharmacy installation of RSUD I.A Moeis Samarinda. Based on the formulation of the problem and the basis of the theory that has been stated in this study is the control of drug supplies in the pharmaceutical installation unit of RSUD I.A Moeis Samarinda not in accordance with the elements of internal control.               This type of research is a comparison method which compares the internal control system applied to the pharmacy installation of RSUD I.A Moeis Samarinda with an internal control system according to the theory and uses a flow chart. Also included is a questionnaire-shaped interview process according to data using question and answer with related sections.            Based on the results of the analysis, the system and accounting procedures for drug inventories at the RSA I.A Moeis pharmaceutical installation unit in Samarinda are in accordance with the elements of internal controln the pharmaceutical installation unit of RSUD I.A Moeis Samarinda not in accordance with the elements of internal control.               This type of research is a comparison method which compares the internal control system applied to the pharmacy installation of RSUD I.A Moeis Samarinda with an internal control system according to the theory and uses a flow chart. Also included is a questionnaire-shaped interview process according to data using question and answer with related sections.            Based on the results of the analysis, the system and accounting procedures for drug inventories at the RSA I.A Moeis pharmaceutical installation unit in Samarinda are in accordance with the elements of internal control